Efektivitas Konseling Prenatal Berbasis Aplikasi Mobile dalam Meningkatkan Kepatuhan Ibu Hamil Mengonsumsi Suplemen Zat Besi - Atika, Zummatul; Ula, Zumrotul (Barongko: Jurnal Ilmu Kesehatan, 2025)
Anemia in pregnant women remains a public health problem that impacts both the mother and the fetus. One way to prevent anemia is to regularly consume iron supplements. However, compliance with iron supplementation among pregnant women remains low. The use of information technology through mobile applications offers an innovative alternative for providing prenatal counseling. This study aims to determine the effectiveness of mobile application-based prenatal counseling in improving compliance with iron supplementation among pregnant women. This study used a quantitative design with a quasi-experimental approach. The sample size was 50 pregnant women, divided into an intervention group and a control group. Data were collected using an adherence questionnaire and analyzed using statistical tests. The results showed an increase in compliance with iron supplementation in the group receiving mobile application-based counseling compared to the control group (p < 0.05). The conclusion of this study is that mobile application-based prenatal counseling is effective in improving compliance with iron supplementation among pregnant women.